The impact of response to intervention on English language learners in urban elementary schools. - Schimpf, Laura (2015)
ABSTRACT: This paper examines the impact of Response to Intervention practices on English language learners in urban elementary schools across the United States. Response to Intervention practice is encouraged by both researchers and the federal government to support students who are at risk for falling behind in academic areas such as reading. Further, Response to Intervention claims to effectively separate students who can be supported through learning interventions in the general education classroom and students who need special education services. Due to the disproportionality of ethnic and racial minorities in special education, many of whom attend urban schools and whose native language is not English, Response to Intervention practice is argued to be the most effective way of reducing this disproportionality by directly supporting those students. To examine these arguments and claims, this paper systematically reviews ten research studies that report the impact that RTI interventions have had on English language learners in urban elementary schools. The results are analyzed to determine in reading skills are improved, if students are supported by RTI practices to avoid being mislabeled as having a specific learning disability, and the standards needed to maintain efficiency by teachers and school districts. Further, a comparison is drawn between the results of English language learners in urban elementary schools and their native English-speaking counterparts and students not in the urban elementary setting. After a thorough analysis of the literature, limitations and implications for future practice are discussed.